RELATIONS OF STRUCTURE COMPONENTS OF GIANT RADIO SOURCES - Miroshnichenko, A. P. (Одеські астрономічні публікації, 2016)
Our previous estimates of physical parameters of galaxies and quasars with steep radio spectrum have showed their great radio luminosity and giant radio structure. Examination of the relations of corresponding monochromatic luminosities at different bands (from decametre to X-ray) allows estimate the comparative contribution of emission of structure components of sources. Using the sample of galaxies and quasars with steep radio spectrum from the UTR-2 catalogue we determine the contribution of emission of extensive radio lobes relatively central region, also relatively accretion disk, gas-dust torus, crown of accretion disk of given source. The particular interest has the relation of monochromatic luminosities of objects at near-infrared and Xray bands, which corresponds to contribution of emission of gas-dust torus relatively emission of crown of accretion disk. The derived estimates of contribution of emission of components of giant sources reveal evolution effects at relations on redshift, linear size, age of examined sources.